2015
DOI: 10.3390/foods4040645
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial, Antioxidant, and Anti-Inflammatory Activities of Essential Oils of Selected Aromatic Plants from Tajikistan

Abstract: Antimicrobial, antioxidant, and anti-inflammatory activities of the essential oils of 18 plant species from Tajikistan (Central Asia) were investigated. The essential oil of Origanum tyttanthum showed a strong antibacterial activity with both minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values of 312.5 µg/mL for E. coli, 625 µg/mL (MIC) and 1250 µg/mL (MBC) for MRSA (methicillin-resistant Staphylococcus aureus), respectively. The essential oil of Galagania fragrantissima … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…The essential oil of T. vulgare demonstrated antioxidant activity by significantly inhibiting the oxidation of DCFH induced by tert-butylhydroperoxide with an IC 50 of 51 µg·mL −1 ( Table 2 ). Using in vitro methods including DPPH, ABTS, and FRAP assays, Shaparov et al [ 32 ] also reported a moderate level of antioxidant activity of T. vulgare essential oil. Unfortunately, the chemical composition of the oil was not analyzed and the compounds responsible for the activity were not identified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The essential oil of T. vulgare demonstrated antioxidant activity by significantly inhibiting the oxidation of DCFH induced by tert-butylhydroperoxide with an IC 50 of 51 µg·mL −1 ( Table 2 ). Using in vitro methods including DPPH, ABTS, and FRAP assays, Shaparov et al [ 32 ] also reported a moderate level of antioxidant activity of T. vulgare essential oil. Unfortunately, the chemical composition of the oil was not analyzed and the compounds responsible for the activity were not identified.…”
Section: Resultsmentioning
confidence: 99%
“…Antibacterial activity of T. vulgare from Roumania [ 9 ] and Slovakia [ 38 ] were also reported against gram-positive bacterial strains using the disc diffusion method. Moreover, T. vulgare essential oil from Tajikistan was found to be weakly effective against E. coli and MRSA [ 32 ]. In our study, we used a new antibiotic assay developed to test hydrophobic compounds as described in the Material and Methods section [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The essential oils of many plants are known to have antimicrobial activity [ 4 , 36 , 37 ], which could act as a chemical defence against various pathogens. The present study examines the antimicrobial activities against all tested strains, which may be attributed to the presence of sesquiterpenes such as (E) - β -caryophyllene or germacrene D in the tested oils.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, antioxidant properties and anti-inflammatory effect was evaluated using different methods. 5-LOX was inhibited by Z. clinopodioides esstential oil (could be due to the presence of compounds structurally related to fatty acids serving as substrate of LOX) [420].…”
Section: O Hmentioning
confidence: 99%